Activation of Dihydrogen by Masked Doubly Bonded Aluminum Species. Issue 41 (16th August 2016) - Nagata, Koichi; Murosaki, Takahiro; Agou, Tomohiro; Sasamori, Takahiro; Matsuo, Tsukasa; Tokitoh, Norihiro
Abstract: Activation of dihydrogen by masked dialumenes (Al=Al doubly bonded species) is reported. Reactions of barrelene‐type dialumanes, which have the reactivity as masked equivalents of 1, 2‐diaryldialumenes ArAl=AlAr, with H2 afforded dihydroalumanes ArAlH2 at room temperature (Ar: bulky aryl groups). These dihydroalumanes form hydrogen‐bridged dimers [ArHAl(μ‐H)]2 in the crystalline state, while a monomer–dimer equilibrium was suggested in solution. The 1, 2‐diaryldialumenes generated from the barrelene‐type dialumanes are the putative active species in the cleavage of H2 . Abstract : Cut in half by the masked magician : Homolytic dihydrogen splitting was achieved by using barrelene‐type dialumanes which serve as masked Al=Al doubly bonded species under ambient conditions. The generated dihydroalumane dimers are presumably in equilibrium with the corresponding monomers in solution.